Virtual Sound Localization by Blind People - Larisa DUNAI; Ismael LENGUA; Guillermo PERIS-FAJARNÉS; Fernando BRUSOLA (Archives of Acoustics)
The paper demonstrates that blind people localize sounds more accurately than sighted people by using monaural and/or binaural cues.